Pelatihan Pembuatan Hantaran Pernikahan Sebagai Peningkatan Perekonomian Di Kelurahan Bandungrejo, Kecamatan Mranggen Kabupaten Demak - Dyah Ika Kirana Jalantina; Maria Magdalena Minarsih (Jurnal Pengabdian kepada Masyarakat STIE AKA Semarang, 2025)
Wedding gifts in the form of various women's necessities are usually given by the groom to the bride on the night before the wedding. These gifts are generally formed and decorated in such a way that they are aesthetic and unique. This wedding gift making service can be done at home as an activity that can increase income. This wedding gift making training is carried out by practicing directly with local comunity in Bandungrejo Village, Mranggen District by bringing in trainers who have this expertise. The purpose of this training is to stimulate creativity and innovation in order to produce attractive gifts that are in demand by the community and ultimately generate additional income.